The Current Unilateralist Counterattack on Unionism and Collective Bargaining - Barkin, Solomon (Relations Industrielles / Industrial Relations, 1986)
The swing to political conservatism in the eighties encouraged anti-union groups to weaken and dismantle both the union movement and the labor parties. The author, in his analysis, illustrates the developments and contents of the new policies in the field of industrial relations noting that another equally dramatic account may be set forth in the fields of wage policy and social welfare programs.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Collective bargaining; Conservatism; Labor Unions; Labor relations; Manycountries; Politics; Public policy; Unions